Optimalisasi Supervisi Kepala Ruangan dalam Pelaksanaan Edukasi Personal Hygiene untuk Keluarga dan Pasien - Mastia Wiraya; Krisna Yetti; Anik Maryunani (Journal of Telenursing (JOTING), 2023)
This research aims to design an innovation that can improve the planning function of the supervision program by the head of the room by making educational videos for families and patients to create patient independence. The method used is the case study method. This research begins with studying problem identification, problem analysis, and prioritization of problems to be analyzed using fishbone. The next stage of the strategy will be planned by preparing a Plan of Action, and then implementation will be carried out. The results showed that the activities of bathing patients in bed were rare (52.9%), washing the patient's hair was rare (76.5%), care for feet, hands, and nails was rare (64.7%), care for eyes, ears, and nose was occasional ( 64.7%) and oral and dental care (brushing the patient's teeth) is rare (64.7%). In conclusion, fulfilling personal hygiene needs by nurses in the Depok Hospital inpatient room is in the not optimal category. Keywords: Innovation, Personal Hygiene, Regular Supervision, Educational Videos